2013
DOI: 10.1111/brv.12031
|View full text |Cite
|
Sign up to set email alerts
|

Cellular differentiation and individuality in the ‘minor’ multicellular taxa

Abstract: Biology needs a concept of individuality in order to distinguish organisms from parts of organisms and from groups of organisms, to count individuals and compare traits across taxa, and to distinguish growth from reproduction. Most of the proposed criteria for individuality were designed for ‘unitary’ or ‘paradigm’ organisms: contiguous, functionally and physiologically integrated, obligately sexually reproducing multicellular organisms with a germ line sequestered early in development. However, the vast major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 146 publications
0
62
0
1
Order By: Relevance
“…This is found in the germsoma differentiation in multicellular organisms and worker/queen roles in eusocial insects [12][13][14][15][16][17]. While reproductive specialization is not strictly required for division of labor to provide a fitness benefit to the higher-level entity, it has evolved repeatedly in independent lineages [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This is found in the germsoma differentiation in multicellular organisms and worker/queen roles in eusocial insects [12][13][14][15][16][17]. While reproductive specialization is not strictly required for division of labor to provide a fitness benefit to the higher-level entity, it has evolved repeatedly in independent lineages [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Biological individuality has been a major issue for immunologists since at least the end of the 19 th century (Richet 1894;Richet 1913;Loeb 1930;Loeb 1937;Medawar 1957;Burnet 1962;Hamburger 1978), as emphasized by many historians of the field (Löwy 1991;Moulin 1991;Tauber 1991;Tauber 1994;Löwy 2003). Immunologists have suggested that the immune system is involved in the definition of biological individuality in at least three senses of "individuality" (Pradeu 2012 (Burnet 1962, p. 38-41).…”
Section: Delineating the Physiological Individual: An Immunological Pmentioning
confidence: 99%
“…Leo Loeb shows, in several papers (Loeb 1930;Loeb 1937;Loeb 1953) and in a long book entirely devoted to the topic of biological individuality (Loeb 1945), that there exist degrees of biological difference ("individuality differentials") among individuals, which reflect the uniqueness and unity of each individual, and explain the success or failure of grafts. Medawar, who shared the Nobel Prize with Burnet in 1960 for their work on immune tolerance to grafts, also examines the relation between transplantation and the uniqueness of the individual, an idea further explored by Jean Dausset, who demonstrated the existence of an histocompatibility system in humans (Dausset 1981) (see also (Hamburger 1978)). A striking realization at that time was that biological uniqueness is further reinforced by the fact that even genetically identical individuals have different immune systems (Pradeu 2012).…”
Section: Delineating the Physiological Individual: An Immunological Pmentioning
confidence: 99%
“…For example, in the evolution of multicellularity a new kind of reproducing individual arises, but the parts of these individuals (their cells, and also their genes) remain able to reproduce. Systems in which there is a hierarchy of objects in which both parts and wholes reproduce are the source of debates and puzzle cases, because it may be unclear which units are the bearers of fitness (31)(32)(33). Examples include social insects and their colonies, demes and their constituent organisms, and ramets and genets in botany.…”
Section: Conceptual Frameworkmentioning
confidence: 99%